2019
DOI: 10.1590/s1678-3921.pab2019.v54.00983
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lightweight replacement pullets fed rations with sunflower cake and the addition of enzymes

Abstract: The objective of this work was to evaluate the inclusion of sunflower cake (SC) and the addition of enzymes in the ration of lightweight replacement pullets in the growth phase, as well as their effects on the variables feed consumption and conversion, productive performance, sexual maturity, egg quality at the beginning of the laying phase, and economic viability. Five hundred and forty pullets of the Hy-Line W-36 light line were used. The experimental design was completely randomized, in a 2×2+1 factorial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Using laying hens or pullets in these trials is rare because of the high price of the birds. Of course, the digestion potential of adult roosters, broiler chickens, laying hens, and restricted-fed pullets is different (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Using laying hens or pullets in these trials is rare because of the high price of the birds. Of course, the digestion potential of adult roosters, broiler chickens, laying hens, and restricted-fed pullets is different (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…The growth phase is considered a critical phase within the production system (Freitas et al, 2014), where fibrous feed is provided to control the broilers' excessive weight gain (Braz et al, 2011). Some authors proposed the inclusion of SC in laying pullets (Kargopoulos et al, 2017;Alencar et al, 2019;Souza et al, 2020;Alencar et al, 2021) and demonstrated the possibility of additional studies with SC in white layers' diets. Considering the differences in strains, greater practical application, and a better understanding of the obtained results, adjustments were made to achieve optimal levels without compromising the health and performance of pullets.…”
Section: Introductionmentioning
confidence: 99%